Elective "True Day Case" Laparoscopic Inguinal Hernia Repair in a District General Hospital: Lessons Learned from 1000 Consecutive Cases. (3rd June 2018) - Solodkyy, A.; Feretis, M.; Fedotovs, A.; Di Franco, F.; Gergely, S.; Harris, A. M.
Abstract : Introduction . Laparoscopic inguinal hernia repair (LIHR) is ideal for day case surgery. It is recommended that at least 70% should be day cases as a measure of cost-effectiveness. The aims of this study were to (i) assess the rate of true day case (TDC) surgery and (ii) identify predictors associated with unexpected overnight stay (UOS). Methods . Data was collected prospectively on 1000 consecutive elective LIHR performed in a District General Hospital (DGH) over a 7-year period. Data was collected on baseline patient demographics, ASA grade, and intraoperative details. A multivariate analysis was performed in order to identify predictors of UOS. Results . 1000 patients (927 males) underwent elective LIHR. Mean age was 57.3±15.2 years. 915 patients were planned as day case procedures. 822/915 day cases (89.8%) were discharged on the same day and 93 (10.2%) stayed overnight unexpectedly. Patient age, duration of procedure, and patient slot in the operating list were found to be independent predictors (p<0.05) of UOS. Conclusion . Our results demonstrate that LIHR is a "true" day case procedure in a DGH. Although some factors associated with UOS cannot be altered, careful patient selection and operating list planning are of paramount importance in order to minimise the burden on healthcare resources.